Pengaruh Harga dan Gaya Hidup terhadap Keputusan Pembelian Iphone Second - Setiawan, Rahmat Imam; Haris, Ibnu; Sutrisno (SAFE-Network, 2025)
This analysis focuses on assessing how price and lifestyle affect consumer decisions related to acquiring used iPhones in Tangerang City, employing a quantitative strategy through a survey with 97 participants selected by purposive sampling. Data were collected via surveys and examined using multiple linear regression, t-tests, F-tests, and the coefficient of determination. This results indicate that price and lifestyle have a positive impact on purchase decisions. The coefficient of determination of 9.5% indicates that both variables explain the variation in purchase decisions, while the remainder is influenced by other factors. As a result, it is evident that price holds a positive and marginally significant effect, while lifestyle has a positive but insignificant impact on purchase decisions. These findings indicate that price and lifestyle factors still need to be considered in influencing consumers to purchase second-hand iPhones.